To evaluate and compare the synergetic effect of Cranberry extract with PRF versus the use of PRF alone in the treatment of Chronic Periodontitis: A Clinical and a Radiological study - Prachi Khuntia; Rashmita Nayak; Saurav Panda; Abhaya Chandra Das; Rinkee Mohanty (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Among the several types of periodontitis, chronic periodontitis is the utmost common form of periodontal disease which can progress with a slow rate but may have a sudden rapid rate of progression along with a remarkable bone loss. In terms of adequacy in sufficient periodontal regeneration, periodontal flap surgeries lack the potential and takes often a back seat. Several other regenerative methods have been promoted among which platelet rich fibrin (PRF) is seen to be most extensively used. It is an old and successful trend to either add PRF or to infuse it along with other drugs at the wound site to enhance periodontal regeneration. Several herbal products were used as an infusion with PRF in the past for the antimicrobial effect but no herbal products were used in the form of a synergetic agent with PRF for enhancing periodontal regeneration. Cranberry fruit, its origin is from North America has been much popular because of its essential ingredients for a good health. It has got a significant therapeutic potential as an antimicrobial agent and as an antioxidant agent, but been never used for enhancing periodontal regeneration. Hence, the current study’s goal is to assess and compare the synergetic effect of Cranberry extract with PRF versus the use of PRF alone in the treatment of chronic periodontitis. Materials and Method: A double blinded randomized clinical trial (RCT) was done with twenty subjects which included patients based on the selection criteria in the age group of 35 to 55 years having periodontal intrabony defects. The Control Group A received PRF alone and the Test Group B received PRF+CRN at the site of intrabony defects.Subjects in each group were assessed for their clinical parameters such as probing pocket depth (PPD), relative attachment level (RAL), gingival index (GI), plaque index (PI) and radiographical parameters such as defect depth (DD), defect area (DA) and defect fill % (DF %) at baseline. The follow up period was decided according to the the previous studies at three, six and nine months respectively. Results: There was a statistically significant enhancement in the clinical and radiographic parameters from baseline to three, six and nine months in each group. However, the treated group showed statistically significant than the control group. Conclusion: Within the limitations of the given study, use of PRF+CRN was efficacious in comparison to the use of PRF alone in the treatment of intrabony defect.